Effects of Bilateral M1 Anodal Transcranial Direct Current Stimulation on Pain and Mood in Patients with Non-Specific Chronic Low Back Pain - LU Xuefang; YUAN Peng; DENG Shukun; SU Qiuju; FANG Xiangming; CHEN Gangrui; YANG Han; SHEN Ying (康复学报)
ObjectiveTo observe the effects of a novel transcranial direct current stimulation (tDCS) device known as "Halo Sport" on pain and mood in patients with non-specific chronic low back pain (NSCLBP), by specifically targeting the bilateral primary motor cortex (M1 region).MethodsForty-two patients with NSCLBP who were treated in the Rehabilitation Medicine Department of Wuxi People's Hospital Affiliated to Nanjing Medical University from July 2023 to March 2024 were recruited. According to the random number table method, the patients were divided into control group and experimental group, with 21 patients in each group. During the course of treatment, one patient withdrew in each group and 20 patients were included in both groups. The experimental group received treatment using the new "Halo Sport" tDCS at 2.0 mA for 20 minutes with bilateral M1 anodes, followed by 45-minute exercise treatment, including 5 minutes of stretching exercises, 20 minutes of core training exercises, and 20 minutes of aerobic training exercises. The control group received sham tDCS in combination with exercise therapy. The treatment period for both groups was three days a week for four weeks. Before and after 4 weeks of treatment, the numerical rating scale (NRS) was used to evaluate pain intensity, the oswestry disability index (ODI) was used to evaluate lumbar dysfunction degree, while the pain catastrophizing scale (PCS), self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were used to assess related negative emotions.Results1) Pain intensity: After treatment, the NRS scores in the experimental and control groups significantly decreased compared with those at the baseline (P<0.05). The difference of NRS score in the experimental group was significantly higher than that in the control group (P<0.05). 2) Lumbar dysfunction degree: After treatment, ODI scores of the experimental and control groups significantly decreased compared with those at the baseline (P<0.05). However, the difference of ODI scores between the two groups was not statistically significant (P>0.05). 3) Negative emotions: After treatment, both groups showed a significant decrease in PCS, SDS and SAS scores compared to the baseline (P<0.05), while the difference of PCS, SDS and SAS scores between the two groups was not statistically significant (P>0.05).ConclusionBilateral M1 area anodal tDCS with the Halo Sport device can significantly reduce pain in patients with NSCLBP. Whether combined with tDCS or not, exercise therapy can improve lumbar spine dysfunction and alleviate negative emotions in NSCLBP patients.